First Coronavirus Active Survey in Rodents From the Canary Islands - Monastiri, Abir; Martín-Carrillo, Natalia; Foronda, Pilar; Izquierdo-Rodríguez, Elena; Feliu, Carles; López-Roig, Marc; Miquel, Jordi; Ar Gouilh, Meriadeg; Serra-Cobo, Jordi (Frontiers in Veterinary Science, 2021)
Since the beginning of the 21st century five new coronaviruses inducing respiratory diseases in human have been reported. These emergences promoted research on coronaviruses in wildlife. We started the first eco-epidemiological study to screen the coronaviruses circulating in mice and rats of four Canary Islands. Between 2015 and 2019, we obtained fecal samples of three rodent species captured in urban and rural areas. Fecal samples were analyzed by nRT-PCR and the resulting sequences were compared to known diversity using Bayesian phylogenetic methods. We only found RNA of coronavirus in house mice from El Hierro (10.53%), Tenerife (7.02%) and Lanzarote (5.26%) islands. All coronaviruses detected belong to the species Murine coronavirus belonging to the genus Betacoronavirus and subgenus Embecovirus. All positive house mice were captured in anthropogenic environment. The phylogenetic analysis shows that murine coronaviruses from Canary Islands are related with some European coronaviruses. Albeit data are still scarce in the region, the most probable origin of Murine coronavirus in Canary Island is continental Europe. According to temporal Bayesian phylogenetics, the differentiation between Canary and continental viruses seems to be quite recent. Moreover, murine coronaviruses from El Hierro, Tenerife and Lanzarote islands tend to segregate in different clades. This enlightens the potential role of rodents or other possibly invasive species in disseminating infectious diseases to remote places through exchanges with the continent. It is important to consider these aspects in the sanitary control of islands, for health and biodiversity preservation concerns.